Investigating Participation to Strengthen Transition-Specific Collaboration Among Rehabilitation Professionals for Improved Outcomes. - Oertle, Kathleen Marie (Journal of Applied Rehabilitation Counseling, 2026)
The demand for vocational rehabilitation transition services is growing, resulting in greater attention to rehabilitation professionals' participation. Meeting the service needs of the transition-age population requires that rehabilitation professionals address change and sometimes completely new expectations. Collaboration with secondary educators is among these expectations, as is working with students and parents. Yet coordinated collaboration among rehabilitation professionals is needed to maximize the use of resources for effectiveness. In this mixed-methods investigation, rehabilitation professionals' reasons for participation in transition education and services are described as distinctive ways in which they can assist and collaborate with each other. Recommendations include attention to, training for, and research on collaboration among rehabilitation professionals, in addition to collaboration with students/youth and their families, as well as educators. These findings can be used for connecting the secondary preparation and planning process with activities leading to postsecondary outcomes. This research advances the transition-specific collaboration discussion to more commonly and intentionally include all rehabilitation professionals participating in transition, such as transition specialists, community rehabilitation providers, and Centers for Independent Living personnel.